2013
DOI: 10.1161/strokeaha.112.672923
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Cooling With a Passive Head and Neck Cooling Device

Abstract: Background and Purpose— Therapeutic hypothermia improves clinical outcome after cardiac arrest and appears beneficial in other cerebrovascular diseases. We conducted this study to investigate the relationship between surface head/neck cooling and brain temperature. Methods— Prospective observational study enrolling consecutive patients with severe ischemic or hemorrhagic stroke undergoing intracranial pressure (ICP) and brain temperature monitoring. Art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…Moreover, selective brain cooling is potentially applicable for prolonged clinical use, for brain selective mild hypothermia following cardiac arrest and prevent fever in critically ill neurologic patients. There is therefore growing interest in developing novel methods to effectively administer brain hypothermia and temperature control [810]. Accordingly, our objective was to analyze the feasibility of a portable cooling method to control the temperature of the brain via controlling the temperature of the blood flowing through the neck.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, selective brain cooling is potentially applicable for prolonged clinical use, for brain selective mild hypothermia following cardiac arrest and prevent fever in critically ill neurologic patients. There is therefore growing interest in developing novel methods to effectively administer brain hypothermia and temperature control [810]. Accordingly, our objective was to analyze the feasibility of a portable cooling method to control the temperature of the brain via controlling the temperature of the blood flowing through the neck.…”
Section: Introductionmentioning
confidence: 99%
“…Selective brain cooling may prevent the systemic complications seen in whole-body cooling and decrease induction time decreasing risk. Poli et al (2013) describes the effects of a cold gel-filled head and neck wrap on the brain temperature of stroke patients. Findings demonstrated a rapid decrease in brain temperature; however, this temperature change was often accompanied by increases in blood pressure and intracranial pressure possibly from vasoconstriction response to the cold.…”
mentioning
confidence: 99%
“…Numerous factors, such as the duration of hypothermia as well as the method of hypothermia employed, can determine the outcomes. Even the logistics of the hypothermia equipment are crucial for the assessment of safety and efficacy of a hypothermia procedure (Poli et al, 2013). Nevertheless, the effect of hypothermia on an otherwise healthy cortex if the hypothermia treatment is targeting the spinal cord remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Poli et al reported the effects on cortical temperature due to a head-neck cooling device in 11 patients for treatment of severe ischemic or hemorrhagic stroke. Although the treatment LOCAL AND GENERAL HYPOTHERMIA TEMPERATURE PROFILESonly minimally affected cortical temperature (-0.36°C after 49 minutes), patient side-effects included severe hypertension, intracranial pressure crisis (>20 mmHg), and decreased cerebral perfusion pressure (Poli et al, 2013). It is therefore imperative that the effects of general hypothermia on the cortex are well understood, even when used to treat SCI, as the treatment will inevitably induce temperature changes in other regions of the CNS.…”
Section: Discussionmentioning
confidence: 99%